DAYA SAING KOMPARATIF DAN KOMPETITIF INDUSTRI KECIL GULA KELAPA - Romdon, M. Mustopa (Jurnal AGRISEP, 2004)
Development   of small-scale   coconut  sugar  industry  take into  account  as national  sector  in economic  region development    planning   has to  comparative    and   competitive    advantages.eEspecially,      expectation    to  gill contribution    enough   to  prosperity   improvement.    Using   The  Policy  Analysis    Matrix   (PAM)   approaches,    thl study    was   aimed    to   measure    the   comparative     advantage    and   the   impact    government's     policies    in development    on  coconut   sugar  in  Banyumas.    Its  expected   to  contribution    to  development    of  smail-scalE industry  specially  coconut-sugar   industry  at Banyumas   regency.   The results  showed  that small-scale   coconu: industries    had   having   positive   profits   both private    and   social   and   had   comparative    and   compettitiv~ advantages.   While  impact  of government   policy  to the small-scale   industry   rise  in toim of price  of input  and output.   Impact   on  input  and  output  price   respectively    indicated   that  producer    (tappers)   didn't   take  input subsidy  and experienced   disincentive   in coconut  sugar  production.   It could  be concluded   that the government policy  didnot  fully  supported   development   of small-scale   coconut  sugar  industry,   its  marked  by lowest  privat value-added    than   social    value-added    which  could    be  taken   by   actors    (tappers).    For   supporting    the development    of  the   industry    are  needed   reorientation    and   integrated    mechanism    of  institution    mainlyempowering   and marketing  institution  at least